Ceramics imitating glass? Ribbed bowls made of pottery from Brigantium/Bregenz - Rabitsch, Julia (Rei Cretariae Romanae Fautorum Acta, 2022)
The present paper gives an insight into preliminary results of the analysis of ribbed bowls made of pottery based on the findings from Brigantium/ Bregenz. Therefore, different aspects of research are taken into account: the paper will provide an overview of the known finding spots and the possible origins of the ribbed bowls will be discussed. The indisputable similarity with ribbed glass bowls Isings 3a/b suggests a close relation between them. Since the ribbed bowls from Bregenz are the only ones in the Roman province Raetia pXRF-analyses were carried out to determine their origin. The results show that these bowls were produced locally which is indicated by the same chemical composition as the pre-established reference group from Bregenz. The very rare occurrence of this kind of pottery could stand for the personal preference of single costumers.